Investıgatıon of Balance Performance in Soccer in Terms of Posıtıonal Dıfferences - Ömer Çalışkan; Veysel Böge (Selcuk University, 2023)
The aim of this study was to determine the dominant and non-dominant foot data in young soccer players and to investigate their relationship with each other. For this purpose, 14 healthy young male soccer players participated in the study. The mean age of the participants was 16.50± 1.09 years, mean height was 175.64± 5.48 cm, and mean body weight was 65.64± 9.47 kg. The study protocol was approved by the ethics committee of Selçuk University, Faculty of Sport Sciences. Dynamic balance tests with eyes open (GA) and eyes closed (SC) were used to evaluate the balance performances of the athletes. In the data obtained as a result of the tests, the significance of the difference between the dominant and non-dominant foot static balance parameters of the soccer players was tested with Paired Sample T test. While there was no difference in dynamic balance parameters in all values of dominant and non-dominant leg, significant differences were found in all parameters except ML parameter in dynamic balance tests performed with eyes open and eyes closed.